Perencanaan Perkerasan Kaku (Rigid Pavement) Dengan Menggunakan Wiremesh Pada Ruas Jalan HOS. Cokroaminoto Dan Jalan Moch. Yamin (Tuban) - Sulaiman, Kristedy Permana; Wasono, Sapto Budy (Universitas Dr. Soetomo, 2019)
Highway is one of the land transportation infrastructure which plays an important role in human life in the field of transportation. Jalan Hos. Cokroaminoto and Jalan Moch. Yamin is a national road that fights important to support the economic flow of the surrounding region and also other cities.The author will compare the calculations using two methods, namely the Bina Marga Method 2002 and the AASHTO 1993 method in order to obtain the value of pavement, besides that it also wants to see which method is more efficient and economical in terms of pavement thickness and cost.From the results of the road pavement planning used, the thickness of the pavement is according to the planned 20-year age from 2017 to the end of the year plan for 2037. Economic factors also taken into account in this analysis include the 1993 AASHTO Method.The input parameters of pavement thickness planning for the 1993 AASHTO method are traffic parameters, subgrade reaction modulus, pavement construction material, reliability, and drainage coefficient. For the Jalan Hos section. Cokroaminoto and Jalan Moch. Yamin concrete plate thickness based on the calculation of the 2002 Bina Marga method is 20 cm, while based on the 1993 AASHTO method it is 29 cm. The difference obtained is quite large, namely 9 cm. This is due to differences in the input parameters of each method. Based on the survey that has been done, the thickness of the existing concrete slab is 29 cm, the thickness is the same as the results of calculations using the AASHTO 1993 method.